2018
DOI: 10.4049/jimmunol.1701738
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Elevated Leptin during Diet-Induced Obesity Reduces the Efficacy of Tumor Immunotherapy

Abstract: Various malignancies are reproducibly cured in mouse models, but most cancer immunotherapies show objective responses in a fraction of treated patients. One reason for this disconnect may be the use of young, lean mice lacking immune-altering comorbidities present in cancer patients. Although many cancer patients are overweight or obese, the effect of obesity on antitumor immunity is understudied in preclinical tumor models. We examined the effect of obesity on two immunotherapeutic models: systemic anti-CTLA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…One potential explanation for this discrepancy is that leptin may have different effects in the context of lean compared to obese organisms due to chronic exposure to elevated leptin levels with obesity. This hypothesis is supported by the observations that intratumoral leptin delivery provides no benefit in obese mice, in contrast to controls ( Rivadeneira et al, 2019 ), and that neutralization of leptin improves immunotherapy responsiveness in mice with diet-induced obesity ( Murphy et al, 2018 ). Further supporting the notion that leptin may reduce CD8 + T cell anti-tumor function in the context of obesity, a recent study found that leptin contributes to CD8 + tumor-infiltrating lymphocyte (TIL) dysfunction in a spontaneous breast cancer model ( Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…One potential explanation for this discrepancy is that leptin may have different effects in the context of lean compared to obese organisms due to chronic exposure to elevated leptin levels with obesity. This hypothesis is supported by the observations that intratumoral leptin delivery provides no benefit in obese mice, in contrast to controls ( Rivadeneira et al, 2019 ), and that neutralization of leptin improves immunotherapy responsiveness in mice with diet-induced obesity ( Murphy et al, 2018 ). Further supporting the notion that leptin may reduce CD8 + T cell anti-tumor function in the context of obesity, a recent study found that leptin contributes to CD8 + tumor-infiltrating lymphocyte (TIL) dysfunction in a spontaneous breast cancer model ( Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 84%
“…Surprisingly, although obesity reduces the anti-tumor immune response, the efficacy of ICB cancer immunotherapy is enhanced in both animal models and human obesity in multiple cancer types ( McQuade et al, 2018 ; Wang et al, 2019 ; Xu et al, 2019 ; Figure 5 ). However, not all studies have found enhanced efficacy of ICB immunotherapy in mice with diet-induced obesity ( Murphy et al, 2018 ). This may be explained by several differences, including the mouse strain (BALB/c versus C57/BL6), cancer model (renal cell carcinoma versus melanoma and lung carcinoma models) and modalities of immunotherapy (anti-CTLA-4 combined with other immunostimulants versus anti-PD-1) ( Murphy et al, 2018 ; Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased leptin in the obese mice was implicated in mediating the PD-1 expression and T cell exhausted phenotype [21]. In contrast, treatment response to CTLA-4 blockade was not improved in diet-induced obese mice, however when leptin was neutralized in this model an increase in the co-stimulatory molecule CD86 was observed as was the response to anti-CTLA therapy [79]. In both models, leptin is implicated in inducing an immunosuppressive microenvironment by increasing PD-1 expression and decreasing immune-stimulatory molecules.…”
Section: Immunotherapymentioning
confidence: 92%
“…Obesity not only induces an increase in tumor infiltration of MDSCs but also MDSC expression of PD-L1 thereby inhibiting anti-tumor responses and promoting tumor growth and metastasis [77]. In a preclinical melanoma model diet induced obesity led to a leptin-dependent decrease in functional DCs and tumor infiltrating CD8+ T cells indicating impairment of an anti-tumor response [79]. A recent study in a mouse melanoma model demonstrated that the frequency of CD8+ T cells expressing exhaustion markers (PD-1, TIM3 and LAG3) were significantly higher both at the tumor site and systemically in obese mice compared to their lean counterparts implicating leptin as the mediator [21].…”
Section: Impact Of Body Fat On the Melanoma Immune Microenvironmentmentioning
confidence: 99%